<h2>
Answer: 2.8 miles</h2>
Step-by-step:
We can write it in the proportion ![\frac{7}{60} = \frac{x}{24}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B60%7D%20%3D%20%5Cfrac%7Bx%7D%7B24%7D)
where x is our number of miles trying to find
We now cross multiply or use the butterfly method which I will demonstrate both
<h3>Cross Multiply</h3>
We multiply the numerator with the dominator
so ![7 multiplied by 24](https://tex.z-dn.net/?f=7%20multiplied%20by%2024)
and ![60 multiplied by x](https://tex.z-dn.net/?f=60%20multiplied%20by%20x)
![7*24=60x](https://tex.z-dn.net/?f=7%2A24%3D60x)
![168=60x](https://tex.z-dn.net/?f=168%3D60x)
![\frac{168}{60} =\frac{60x}{60}](https://tex.z-dn.net/?f=%5Cfrac%7B168%7D%7B60%7D%20%3D%5Cfrac%7B60x%7D%7B60%7D)
or ![x=2.8](https://tex.z-dn.net/?f=x%3D2.8)
Now for the
<h3>Butterfly Method </h3>
You would do 7 times 24 divided by 60 or ![\frac{7*24}{60}](https://tex.z-dn.net/?f=%5Cfrac%7B7%2A24%7D%7B60%7D)
Then
simplify
so 2.8 miles in either method
Triangle ABC is translated 3 units right and 2 units up
by looking at point A (-4,5) which is translated to A'(-1,7)
we can tell by looking at the points that -4 is shifted by 3 units to the right ti reach -1 and 5 is shifted upwards by 2 units to reach 7
Answer:
Step-by-step explanation:
(x₁, y₁) = (-2 , -5) & (x₂ , y₂) = (-3 , 1)
Midpoint = ![(\frac{x_{1}+x_{2}}{2},\frac{y_{1}+y_{2}}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7Bx_%7B1%7D%2Bx_%7B2%7D%7D%7B2%7D%2C%5Cfrac%7By_%7B1%7D%2By_%7B2%7D%7D%7B2%7D%29)
![=(\frac{-2 + [-3]}{2} ,\frac{-5 + 1}{2})\\\\\\=(\frac{-5}{2} , \frac{-4}{2})\\\\=(-2.5, -2)](https://tex.z-dn.net/?f=%3D%28%5Cfrac%7B-2%20%2B%20%5B-3%5D%7D%7B2%7D%20%2C%5Cfrac%7B-5%20%2B%201%7D%7B2%7D%29%5C%5C%5C%5C%5C%5C%3D%28%5Cfrac%7B-5%7D%7B2%7D%20%2C%20%5Cfrac%7B-4%7D%7B2%7D%29%5C%5C%5C%5C%3D%28-2.5%2C%20-2%29)
The width of the rectangular bathroom tile is 11 and 2/3 centimeters. Taft is because 2x5 is 10 cm and 1/3x5 is 5/3. 5/3 simplified as a mixed number is 1 and 2/3. 1 and 2/3 combined with 10 is 11 and 2/3 centimeters.
1/2* N= 1/3
⇒ N= (1/3)/ (1/2)
⇒ N= (1/3)* (2/1)
⇒ N= 2/3
The final answer is N= 2/3~